A reliability generalization meta-analysis of Child Oral Impacts on Daily Performances (C – OIDP) questionnaire - Kalyana Chakravarthy Pentapati; Sravan Kumar Yeturu; Hanan Siddiq (Journal of Oral Biology and Craniofacial Research)
Aim: To evaluate the cumulative estimates of reliability and conduct reliability generalization meta-analysis of Cronbach's alpha for the Child Oral Impacts on Daily Performances (C-OIDP) questionnaire. Methodology: Systematic search of four databases from inception to November 30th, 2019 was performed. Studies that reported Cronbach alpha for the C–OIDP were included. Cronbach's alpha for each publication was used for the meta-analysis. I2 and Q statistics were calculated to assess heterogeneity. Meta-analysis was performed using a random-effects model to derive a pooled estimate of Cronbach's alpha. Results: Out of 944 publications, data extraction was done from 33 publications after exclusion. The age range among the included publication was from 6 to 19 years. Cronbach's alpha ranged from 0.53 to 0.9. Majority of the publications (n = 21) reported alpha above the benchmark (0.7 and above). Only two publications used condition-specific C-OIDP questionnaires. Twelve publications used self-administered child-OIDP questionnaires. Most of the studies were at a low risk of bias (n = 29). The cumulative alpha was higher in publications with a low ROB (α = 0.74) than a moderate ROB (α = 0.65) The cumulative alpha was 0.73 (SE = 0.02) with a high heterogeneity among the included publications (I2 = 99.28% and Q = 2048.68; P < 0.001). Conclusion: Overall, the RG estimate of Cronbach's alpha for C-OIDP was above the widely accepted benchmark.